National Report for the International Association of Volcanology and Chemistry of the Earth’s Interior of the International Union of Geodesy and Geophysics 2011–2014. Presented to the XXVI General Assembly of the IUGG - Churikova T.G.; Gordeychik B.N.; Fedotov S.A. (GCRAS Publ, 2015)
In the present National Report, major results are given of research conducted by Russian scientists in 2011–2014 on the topics of the International Association of Volcanology and Chemistry of the Earth’s Interior (IAVCEI) of the International Union of Geodesy and Geophysics. Kamchatka Peninsula with its famous Klyuchevskaya Group of volcanoes is the most volcanically active area in Russia and one of the most active in the world. Majority of researches and scientific results on Volcanology and Geochemistry of the Earth’s Interior during 2011–2014 were achieved in this region including recent data on new Tolbachik fissure eruption in 2012–2013. Besides it, the scientific results on the magmatism outside Russia, which were achieved by Russian scientists, are also included in this review. Major achievements in the chemistry of the Earth, geothermy, geodynamics, geochronology and deep mantle structure are featured. The studies as for the single volcanoes as well the regional observations are outlined. The theoretical and applied efforts connected to the volcanological processes are considered. The main conclusions are illustrated by summarized figures. All the required references are given.